The Effectiveness of Vegetable Neem Leaf Pesticides Against Purple Spot Disease on Onion Plants in The Rain Season - Serlia Nur Abifah; Penta Suryaminarsih; Juniawan (Future Science, 2022)
Purple spot disease is one of the main diseases in leaf onion cultivation. One form of control is carried out by utilizing neem plants, especially the neem leaves which have the potential as vegetable pesticides (fungicides). This study aims to determine the effectiveness of neem leaf vegetable pesticide and to obtain the right concentration of neem leaf vegetable pesticide in controlling purple spot disease on a leaf in rainfall season. This study used an experimental method designed in a single factor Completely Randomized Design (CRD) using neem leaf pesticide consisting of three treatments (control, 10%, and 20%). The results showed that neem leaves at a concentration of 20% were effective as a vegetable pesticide to control purple spot disease on leaf onion. Neem leaf vegetable pesticides at a concentration of 20% were able to inhibit the increase in the area of attack symptoms and also inhibit the intensity of purple spot disease attacks on leaf onion by 13.84%. This is caused by the increase in concentration causing an increase in the content of the active ingredient in the substance which functions as a pesticide that is able to inhibit the spread of large quantities.